P3-S2.03 Clinical evaluation of the BD HSV1 Qx assay for the direct qualitative testing of HSV1 as compared to viral culture and a laboratory-based PCR assay using male and female external anogenital lesions. (10th July 2011) - Pantone, A; Van Der Pol, B; Williams, J; Corey, L; Hook, E; Body, B; Taylor, S; Fine, P; Ginde, S; Lebed, J
Abstract : Background: To compare the performance characteristics of the BD ProbeTecTM HSV1 Qx Assay* on the BD ViperTM System in Extracted Mode to viral culture and a well-characterised molecular assay for the detection of HSV1. External anogenital lesions were sampled with two different collection devices: a universal viral transport (UVT) kit and a BD Qx swab (QS) kit*. Methods: Eleven geographically diverse clinical centers participated in the study, with nine of the sites enrolling participants. The UVT was collected first followed by the QS specimen. A portion of each UVT specimen was transferred to a Qx Diluent tube (diluted UVT) and a cryovial. The remainder of the UVT in the original tube was frozen at −70°C and sent to one of two sites for HSV viral culture using the ELVIS®HSV ID and D3 Typing Test System (Diagnostic Hybrids, Inc). The diluted UVT and QS specimens were shipped to one of three sites for HSV testing on the BD Viper. The UVT aliquot in the cryovial was stored at −70°C and shipped to the University of Washington for PCR testing for HSV. Results: Subjects (n=508) were enrolled from February to August of 2010 with 312 UVT and 308 QS samples available for comparison to ELVIS culture, and 506 and 502 samples, respectively, for comparison to the PCR assay. Samples positive for HSV2 by viral culture did not have results for HSV1 per the ELVIS package insert and were excluded from further analysis. The sensitivity and specificity of the BD HSV1 Qx Assay as compared to ELVIS culture and the positive (PPA) and negative per cent agreement (NPA) of the assay compared to the HSV PCR assays were determined for both specimen types see Abstract P3-S2.03 table 1 . Conclusions: The BD HSV1 Qx Assay on the BD Viper System had excellent agreement with viral culture and the lab developed PCR assay, which is currently recognised as one of the best available tests for the detection of HSV1. A commercially available molecular-based assay for the detection of HSV would not only improve detection and reduce turn-around time on results, but may also obviate the need for stringent transport conditions required for HSV culture. *Product not for sale, for investigational use only in the US.